Bacterial pathogens and antibiotic resistance patterns in children with urinary tract infection admitted at tertiary hospital in Nepal - Shah, Ganesh; Pokhrel, Bhishma; Shah, Anish Kumar; Bista, Puspa Bahadur; Bhattarai, Asmita (Journal of Patan Academy of Health Sciences, 2016)
Introductions: Urinary tract infection (UTI) is a common bacterial infection affecting children. A prompt recognition and accurate antimicrobial management are vital to prevent kidney damage. This study aims to determine the bacterial pathogens and their patterns of antimicrobial resistance in children presenting with UTI. Methods: This was a cross sectional study done at Patan Hospital, Patan Academy of Health Sciences, from Nov 2012 to Oct 2016. There were 88 children between age group of 1 to 14 years with culture proven UTI. The bacterial pathogens and antibiotic resistance were analysed. Results: Three most common organisms isolated were E. Coli 60 (68%), Klebsiella species 15 (17%) and Proteus 7 (8%). The resistance of E. Coli to ampicillin, ofloxacin, cefotaxime, gentamicin and amikacin were 51 (85%), 49 (82%), 45 (75%), 17 (28%) and 2 (3%) respectively. The resistance to ampicillin was Klebsiella species 13 (87%), Proteus 6 (86%) and Enterococcus 3 (60%). Conclusions: The E. Coli was leading bacterial pathogen causing UTI in children, with ampicillin resistance occurring in more than half of these cases. Amikacin and gentamicin had lower antibiotic resistance and can be used for treatment of UTI in children. Journal of Patan Academy of Health Sciences. 2016 Dec;3(2):32-35